The study on production performances of part transporter in flexible manufacturing system by using simulation method - Iqbal, Mohammad; Purnomo, Muhammad Ridwan Andi; Mohd Imra, Muhammad Ammar; Konneh, Mohamed; Karim, A.N. Mustafizul (Trans Tech Publications, Switzerland, 2012)
Material handling is one of major components in Flexible Manufacturing System (FMS). Any improvement of material handling capability is to affect the performance of the whole system. This paper discusses the simulation study on the effect of part arrival rate and dispatching rules to the average waiting time and production rate of the FMS. The facilities of the system were modeled into simulation environment by using Arena Simulation Software. The production parameters such as machine processing times, part transportation speed and type of products were put into the model to represent the behaviors of the real system. Two rules have been considered in the study, i. e. first come first served (FCFS), and shortest processing time (SPT). Average waiting time and productivity were taken into account as performance measures of the system. The result of the study showed that SPT rule gives shorter average waiting time and higher productivity. Based on this result, the SPT rules would be used to control part transporter in order to have a better performance of the FMS.